Evaluation of endometrial cancer based on a multidisciplinary team in Sulaimaniyah, Iraq - Hussein, Shahla Yousif; Fattah, Chro Najmaddin (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Using a multidisciplinary team is a natural progression in cancer care, reflecting the gains achieved by many professions and disciplines and the use of various therapeutic modalities and patient support. Objectives: To investigate the prevalence of endometrial cancer, related risk factors, management, and follow-up before and after multidisciplinary team care (MDTC). Methods: This cross-sectional observational study was conducted on 186 patients with endometrial cancer confirmed by endometrial biopsy cytology (endometrioid/non-endometrioid type). Patient data on clinical, surgical, pathological, and adjuvant therapies were collected, including age, body mass index (BMI), surgical procedure, nodal staging, and final pathological analysis. Assessment of risk factors and clinical follow-up was done by the MDTC method. Results: The patient’s age at menstruation was >12 years in 151 (83.9%) patients and <12 years in 29 (16.1%) patients. No significant difference was observed between the two groups in examining cancer and evaluating risk factors. However, the evaluations in the MTC group were associated with minor changes in order to improve and manage risk factors. Conclusions: The MDTC can be effective in the overall management of endometrial cancer.
Keywords: Endometrial cancer; multi disciplinary team; cross sectional observational study